The Impact of Cashless and Naira Redesign Policies on Economic Development in Federal Capital Territory, Abuja - Folorunso , Olowu Olagunju; Adebayo , Olasupo Mutiullah (Kashere Journal of Politics and International Relations, 2023)
The risk involved in carrying large amounts of physical cash, precious time waste in the bank during financial transaction and lack of proper records about flow of money in circulation were few of the identified challenges of the over-reliance on cash-based economy. Also, the starching of naira notes out of circulation for various nefarious reasons and lack of CBN ability to redesign the naira most especially the higher denomination, which was part of CBN mandate to redesign, create, and circulate new local legal money every five to eight years necessitated the naira redesign policy in Nigeria. The twin policy no doubt resulted into untold hardship for Nigerians as many small-scale businesses folded up. It is against this backdrop that the study examined the impact of cashless and naira redesign policy on economic development in Nigeria. The study adopted survey research design and data were sourced through primary and secondary sources. Population of the study consisted of FCT residents with bank accounts while sample were selected using Research Advisory Table 2006. The findings of the study showed that the naira redesigned, and cashless policy was lofty policy which could propel economic development but was hurriedly implemented. The study also found that instead of the policy solving the existing fiscal and money problem, the twin policy ended up creating others. The work recommended among others that public policy of such magnitude needs to be a well thought out policy with consultation and interface with major stakeholders.